Penerapan Bauran Pemasaran Dalam Meningkatkan Penjualan Batik Khas Bekasi di Dekranasda Kota Bekasi: Penerapan Bauran Pemasaran Dalam Meningkatkan Penjualan Batik Khas Bekasi di Dekranasda Kota Bekasi - Melia; Kristiana Widiawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Abstract. This study aims to examine the implementation of the 4P marketing mix strategy (Product, Price, Place, Promotion) to increase the sales of Batik Bekasi at Dekranasda (National Crafts Council) of Bekasi City. The research employs a descriptive qualitative method, with data collected through observation, interviews, and literature studies. The findings indicate that Dekranasda has effectively applied the marketing mix through the development of high-quality batik products, pricing aligned with quality, direct distribution, and both offline and online promotion. However, online promotions through WhatsApp and Instagram remain suboptimal. To enhance digital marketing, it is recommended to utilize trending platforms such as TikTok and Shopee and to create advertisements or promotional content that can strengthen the image of local products and support the sales growth of Batik Bekasi. Keywords : Marketing mix, Batik Bekasi, Marketing strategy.